Association between muscle-to-visceral fat ratio and vascular elasticity in medical students - Ayudia, Tsabita; Bustamam, Nurfitri; Harjono Hadiwiardjo, Yanti; Agustini Purwaningastuti, Diana (World Nutrition Journal, 2025)
Background: Medical students often adopt lifestyles that contribute to decreased muscle mass and increased visceral fat accumulation, which can negatively impact vascular elasticity, a biomarker for the early detection of cardiovascular disease. Objective: This study aims to evaluate the association between the muscle mass to visceral fat ratio and vascular elasticity in medical students at Universitas Pembangunan Nasional Veteran Jakarta (UPNVJ). Methods: A cross-sectional design was conducted from November 2023 to January 2024 at UPNVJ. The sample consisted of 51 subjects who met the research criteria. The muscle-to-visceral fat (MVF) ratio was measured using Bioelectrical Impedance Analysis (BIA), while vascular elasticity was assessed using the Accelerated Photo plethysmograph Analyzer SA-3000P. Results: The results revealed that 68.6% of the subjects had the lowest MVF ratio and 54.9% exhibited sub-optimal vascular elasticity. No differences were found in age, gender, physical activity, or eating habits between the vascular elasticity groups (p > 0.05). The Chi-square test revealed a significant association between the MVF ratio and vascular elasticity (p = 0.009; OR = 6.545; 95% CI = 1.7–24.9). Conclusion: Students with the lowest MVF ratio were found to be 6.54 times more likely to have sub-optimal vascular elasticity, compared to those with low and high MVF ratios, indicating an increased risk of cardiovascular disease. These findings underscore the importance of early preventive intervention aimed at optimizing body composition through targeted wellness programs. The implementation of nutritional education and structured physical activity initiatives, particularly in young adults, may play a critical role in reducing the risk of cardiovascular disease.